Priority Distortion in Public Budgeting at the Local Level - Simin Simin; Hikmah Nuraini; Shadu Satwika Wijaya; Sendy Noviko (Public Administration, Faculty of Politics and Social Science, Universitas Jenderal Soedirman, Indonesia, 2026)
This study examines the phenomenon of priority distortion in village-level public budgeting in Indonesia, with particular attention to how the Village Fund policy is translated into local development programmes. Although participatory budgeting mechanisms through Village Deliberation Forums (Musyawarah Desa) have been institutionally and procedurally implemented, a persistent discrepancy often emerges between community aspirations and the final budget allocations adopted by village governments. This study aims to analyse the dynamics of the village budgeting process and to identify the factors shaping budget allocation priorities within the broader context of village governance. A mixed-methods approach employing a sequential explanatory design was adopted in Banyumas Regency, Indonesia. The quantitative phase involved a community survey to identify citizens’ development preferences and an analysis of Village Revenue and Expenditure Budgets (APBDes). The qualitative phase consisted of in-depth interviews, observations of village deliberation forums, and a process-tracing approach to examine how citizens’ aspirations were transformed throughout the budget cycle. The findings reveal a substantial gap between community needs and actual budgetary outcomes. Survey results indicate that rural communities consistently prioritised agricultural development (88.9%) and education (72.2%) as their most pressing development needs. However, budget allocations within the APBDes were predominantly directed towards physical infrastructure and territorial development projects. This distortion is driven by local power dynamics, whereby the authority of village heads and the influence of supra-village governmental agendas frequently exert greater influence on final budgetary decisions than the outcomes of citizen deliberations conducted through participatory forums. The study concludes that the effectiveness of participatory budgeting should not be assessed solely through procedural compliance or the formal existence of participatory mechanisms. Rather, it should be evaluated based on the extent to which fiscal allocations genuinely reflect and respond to the substantive needs and priorities of local communities.